The Kurds in the Middle East enduring problems and new dynamics - Gurses, Mehmet; Romano, David, 1969-; Gunter, Michael M. (Kurdish societies, politics, and international relations, 2020)
"In light of the changes that the Kurds and the countries in the Middle East are undergoing, The Kurds in the Middle East: Enduring Problems and New Dynamics provides a comprehensive analysis of the Kurdish-state relations in the four key Middle Eastern countries"--